State Participation in the Ensuring of the Quality Management in the Enterprises of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
The article considers the current problems of the transition to international standards of quality based on state programs aimed at providing sustainable competitiveness of domestic enterprises both domestically and abroad. International standardization is one of the most important elements of modern mechanism of quality control. Standardization System of the Republic of Kazakhstan should be harmonized with international, regional and national systems and to protect the interests of consumers and the state in terms of quality and range of products, services and processes, their safety for human life and health, environmental protection and so on.